Navigating COVID-19 and related challenges to completing clinical trials: Lessons from the PATRIOT and STEP-UP randomized prevention trials. (April 2023) - Salovaara, Priscilla K; Li, Christine; Nicholson, Andrew; Lipsitz, Stuart R; Natarajan, Sundar
Background/Aims: High follow-up is critical in randomized clinical trials. We developed novel approaches to modify in-person visits and complete follow-up during COVID-19. Since these strategies are broadly applicable to circumstances wherein follow-up is difficult, they may help in contingency planning. The objective of this article is to develop and evaluate new approaches to replace detailed, in-person study visits for two trials focused on preventing diabetic foot complications. Methods: A quasi-experimental pre–post design compared approaches for follow-up during COVID-19 to approaches pre-COVID-19. Study subjects were outpatients at two Veterans Affairs Medical Centers. Following a research "hold, " research resumed in February 2021 for Self-monitoring, Thermometry and Educating Patients for Ulcer Prevention (STEP UP) (n = 241), which focused on preventing recurrent foot ulcers, and in April 2021 for Preventing Amputation by Tailored Risk-based Intervention to Optimize Therapy (PATRIOT) (n = 406), which focused on preventing pre-ulcerative and ulcerative lesions. To complete data collection, we shortened visits, focused on primary and secondary outcomes, and conducted virtual visits when appropriate. For STEP UP, we created a 20-min assessment process that could be administered by phone. Since PATRIOT required plantar photographs to assess foot lesions, we conducted short face-to-face visits. We explored differences and assessed proportion completing visit, visit completion/100 person-months and compared COVID-19 to pre- COVID-19 using unadjusted risk ratios, incidence rate ratios, all with associated 95% confidence intervals (CIs). Finally, we report time-to-visit curves. Results: In both studies, participants whose follow-up concluded pre- COVID-19 seemed older than those whose follow-up concluded during COVID-19 (PATRIOT: 68.0 (67.2, 68.9) versus 65.2 years (61.9, 68.5); STEP UP: 67.5 (66.2, 68.9) versus 65.3 (63.3, 67.3)). For STEP UP, we completed 91 visits pre- COVID-19 (37.8% (31.6%, 44.2%)) and 63 visits during COVID-19 (78.8% (68.2%, 87.1%)). This was over 1309 person-months pre-COVID-19, and over 208.8 person-months during COVID-19; the visit completion rate/100 person-months were: pre-COVID-19 7.0 (5.6, 8.5), COVID-19 30.2 (23.2, 38.6); risk ratio: 2.1 (1.7, 2.5); and incidence rate ratio 4.3 (3.1, 5.9). Similarly, for PATRIOT, we completed 316 visits pre-COVID-19 (77.8% (73.5%, 81.8%)) and 27 assessments during COVID-19 (84.4% (67.2%, 94.7%)). This was over 1192.7 person-months pre-COVID-19 and 39.3 person-months during COVID-19. The visit completion rate/100 person-months in PATRIOT were: pre-COVID-19 2.7 (2.4, 3.0), COVID-19 6.9 (4.5, 10); risk ratio 1.1 (0.9, 1.3); incidence rate ratio 2.6 (1.8, 3.8). For both studies, the follow-up curves began separating at < 2 months. Conclusions: We achieved higher completion rates during COVID-19 compared to pre-COVID-19 by modifying visits and focusing on primary and secondary outcomes. These strategies prevent excessive missing data, support more valid conclusions, and improve efficiency. They may provide important alternative strategies to achieving higher follow-up in randomized clinical trials.